2016
DOI: 10.1111/1742-6723.12562
|View full text |Cite
|
Sign up to set email alerts
|

Medical scribes in emergency medicine produce financially significant productivity gains for some, but not all emergency physicians

Abstract: In the present study, scribe usage was associated with overall improvements in primary consultations per hour of 13% per scribed hour, and this varied depending on the physician. There is an economic argument for allocating scribes to some emergency physicians on days, evenings and weekends, not to trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 16 publications
1
25
1
Order By: Relevance
“…There was no significant impact on TAT to discharge or patient LOS 9. These results were similar to a recent study which found a 0.11 Pt/hr increase with scribes 11. Three studies have found reductions in door-to-physician time by 3.6 (4.4%), 7 (9.4%) and 22 min (36%) 12–14.…”
Section: Discussionsupporting
confidence: 87%
“…There was no significant impact on TAT to discharge or patient LOS 9. These results were similar to a recent study which found a 0.11 Pt/hr increase with scribes 11. Three studies have found reductions in door-to-physician time by 3.6 (4.4%), 7 (9.4%) and 22 min (36%) 12–14.…”
Section: Discussionsupporting
confidence: 87%
“…Most cost–benefit analyses of scribes have presumed that the scribe is trained and experienced. These analyses estimate 13%–20% medical productivity gains,1 5 8 13 with overall economic gains based on more patients and increased revenue per patient (in the USA, not Australia) set against salary costs of the scribes.…”
Section: Discussionmentioning
confidence: 99%
“…Their use is being evaluated in many settings: Emergency Departments (EDs) [3][4][5][6][7][8][9][10][11], consultant offices [12][13][14][15], primary care [16,17] and hospital wards [1]. Medical scribes have been found to improve physician productivity [3,4,[8][9][10]12] in most Emergency studies, but not all [5,15]. They have also been useful in most office settings [12][13][14] and wards, but again, not all [15].…”
Section: Background and Significancementioning
confidence: 99%